2015
DOI: 10.1038/srep11525
|View full text |Cite
|
Sign up to set email alerts
|

Human longevity is characterised by high thyroid stimulating hormone secretion without altered energy metabolism

Abstract: Few studies have included subjects with the propensity to reach old age in good health, with the aim to disentangle mechanisms contributing to staying healthier for longer. The hypothalamic-pituitary-thyroid (HPT) axis maintains circulating levels of thyroid stimulating hormone (TSH) and thyroid hormone (TH) in an inverse relationship. Greater longevity has been associated with higher TSH and lower TH levels, but mechanisms underlying TSH/TH differences and longevity remain unknown. The HPT axis plays a pivota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
73
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(77 citation statements)
references
References 40 publications
(56 reference statements)
4
73
0
Order By: Relevance
“…These data agree with the positive association between serum TSH levels and longevity reported in rodents [1][2][3] and euthyroid humans [3][4][5][6][7][8][9]. In line with these observations, rhTSH administration in human visceral adipocytes during 7 days, but not In parallel with these findings, a recent publication demonstrated that TSH administration (48h) in fully differentiated human adipocytes resulted in a significant improvement of mitochondrial biogenesis and function, increasing basal respiration, ATP production and spare respiratory capacity in parallel to increased SIRT1 and mitochondrial biogenesisrelated gene markers [22].…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…These data agree with the positive association between serum TSH levels and longevity reported in rodents [1][2][3] and euthyroid humans [3][4][5][6][7][8][9]. In line with these observations, rhTSH administration in human visceral adipocytes during 7 days, but not In parallel with these findings, a recent publication demonstrated that TSH administration (48h) in fully differentiated human adipocytes resulted in a significant improvement of mitochondrial biogenesis and function, increasing basal respiration, ATP production and spare respiratory capacity in parallel to increased SIRT1 and mitochondrial biogenesisrelated gene markers [22].…”
Section: Discussionsupporting
confidence: 82%
“…In humans, the relationship between hypothyroidism and increased life expectancy has also been observed [4][5][6][7][8][9]. Euthyroid 50 year-old participants with increased levels of TSH had a longer life expectancy than participants with decreased serum TSH levels [4].…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…Notably, the Leiden 85+ study, a cohort study of 85-year-olds with a similar design to our study, found that subclinical hypothyroidism was associated with reduced all-cause mortality and cardiovascular mortality (29). This finding, along with the results of familial studies of the oldest old (7, 38), suggests that an elevated serum TSH may be positively associated with longevity and favorable outcomes in the very old. This led us and others to suggest that there may be age-related differences in the vascular risk associated with a raised serum TSH, with higher risks found in younger individuals that attenuated with advancing age (27, 39, 40).…”
Section: Discussionmentioning
confidence: 83%